2021
DOI: 10.3390/ijerph18063178
|View full text |Cite
|
Sign up to set email alerts
|

Does Supplemental Nutrition Assistance Program Reduce Food Insecurity among Households with Children? Evidence from the Current Population Survey

Abstract: The Supplemental Nutrition Assistance Program (SNAP) is designed to improve household diet and food security—a pressing problem confronting low-income families in the United States. Previous studies on the issue often ignored the methodological issue of endogenous program participation. We revisit this important issue by estimating a simultaneous equation system with ordinal household food insecurity. Data are drawn from the 2009–2011 Current Population Survey Food Security Supplement (CPS-FSS), restricted to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…To address these food insecurity issues, nutrition assistance programs such as SNAP were developed [ 31 ]; however, overall cardiovascular disease (CVD) risk factors such as diabetes remain unchanged. Previous studies showed the prevalence of obesity and diabetes did not decline among SNAP participants [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To address these food insecurity issues, nutrition assistance programs such as SNAP were developed [ 31 ]; however, overall cardiovascular disease (CVD) risk factors such as diabetes remain unchanged. Previous studies showed the prevalence of obesity and diabetes did not decline among SNAP participants [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, we examined whether the association was moderated by SNAP by including an interaction term between the exposure and SNAP and adjusting for the selected confounders. Subsequent subgroup analysis was conducted by SNAP [ 31 ].…”
Section: Methodsmentioning
confidence: 99%
“…The U.S. government has implemented a series of food assistance programs for improving low-income Americans' food security and reducing hunger [15]. The Supplemental Nutrition Assistance Program (SNAP) was designed to alleviate food insecurity and poverty [15,16]. Other federal programs target more specific populations, for example the Special Supplemental Nutrition Program for Women, Infants, and Children for pregnant, breastfeeding and postpartum women, and infants and children up to five years old.…”
Section: Introductionmentioning
confidence: 99%
“…In 2015, food banks already served an estimated 46 million Americans [17]. There has been extensive research examining the effectiveness of food assistance programs on reducing food insecurity, but the findings have been inconsistent [16]. For instance, some studies have found no association between SNAP participation and food security [18,19], whereas others have suggested that SNAP participants have higher [19,20] or lower odds of being food insecure for adults [12,[21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…As a consequence, the nutritional quality of emergency food has been examined by researchers in different charitable organizations in several high-income countries such as Canada [22][23][24][25][26], France [27], Germany [28], Italy [29], the Netherlands [30], the U.K. [31][32][33], the USA [34][35][36][37][38][39][40][41][42], and Australia [18]. In addition to the homeless, members of food-insecure households resort to food banks in emergencies [23,43,44] or use them as long-term food sources [45]. The longer low-income households depend on food assistance programs the more nutritional adequacy evaluations are crucial to determine if the programs meet the clients' (long-term) needs [43].…”
Section: Introductionmentioning
confidence: 99%